Investigating IFRS Compliance in Transitioning Countries: A Qualitative Study - Silvia Petre; Nadia Albu (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Idea: The purpose of the paper is to investigate the institutional context in which companies' compliance with IFRS is created over time. Data: We collected financial and non-financial data from the Bucharest Stock Exchange website, from companies' website and from the media, for three pharma companies listed on the Bucharest Stock Exchange. We focused on the period 2013-2017, given that 2012 is the first year for the IFRS application in Romania in the individual accounts. Tools: We employed the EY (2012) Disclosure Checklist and the Dichotomous approach (Tsalavoutas, 2011) to determine the IFRS compliance index. We mobilize an institutional theory-based framework to analyze the IFRS compliance index. What's new? Our results indicate that the level of compliance is an organizational response to macro-, industry-, and organizational level factors. Moreover, companies face several pressures for compliance with different requirements, and choose to what pressures to comply first. Therefore, compliance with disclosure requirements from some IFRS is a piece in an organizational puzzle, so wider frameworks and analyses are needed to understand organizational responses. So what?: Companies respond with various levels of compliance in emerging economies such as Romania, and understanding the factors influencing compliance is of interest for regulators, auditors, and capital market participants. Contribution: We contribute with a qualitative, institutional-based study to a research stream dominated by archival methods, and bring complementary explanations for organizational levels of compliance with IFRS.
Keywords: M41; 650; IFRS compliance; pharmaceuticals industry; institutional theory; emerging country